2020
DOI: 10.3390/polym12040961
|View full text |Cite
|
Sign up to set email alerts
|

Study on Adsorption and Aggregation in the Mixed System of Polyacrylamide, Cu(II) Ions and Innovative Carbon–Silica Composite

Abstract: The paper presents an original study on adsorption and aggregation phenomena in a mixed system consisting of a macromolecular compound, heavy metal ions and an innovative adsorbent. The authors used ionic polyacrylamides (PAM), Cu(II) ions and carbon–silica composite (C-SiO2) in the experiments. Such a system has not yet been described in the literature and therefore, the article is of significant novelty and great importance. The composite was prepared by mixing phenol–formaldehyde resin with silica and pyrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…The adsorption process is the most used technique due to its efficiency and simplicity [6][7][8]. Several adsorbents have been tested in order to remove copper ion, such as activated carbon [8][9][10], clays [11], apatite [12], composite carbon-silica [13], magnetic materials [14][15][16], silica gel [17], hydroxyapatite [18], zeolites [19] and fly ash [5,20]. Over time, fly ash has been investigated by many researchers as an adsorbent for heavy metal removal [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption process is the most used technique due to its efficiency and simplicity [6][7][8]. Several adsorbents have been tested in order to remove copper ion, such as activated carbon [8][9][10], clays [11], apatite [12], composite carbon-silica [13], magnetic materials [14][15][16], silica gel [17], hydroxyapatite [18], zeolites [19] and fly ash [5,20]. Over time, fly ash has been investigated by many researchers as an adsorbent for heavy metal removal [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Previously performed studies confirmed the usefulness of the hybrid carbon-mineral nanocomposites with metallic elements (especially Si/C/Mn) for the adsorption removal of Cu(II) ions from aqueous solution in poly(acrylic acid) presence [13]. In turn, the carbonsilica composite showed high efficiency of Cu(II) adsorption from the solution containing proteins with different internal stability (ovalbumin and lysozyme) [14], as well as ionic polyacrylamides [15].…”
Section: Introductionmentioning
confidence: 74%
“…The conducted research undoubtedly enriched the knowledge about the possibility of using an innovative carbon-silica composite for dye removal. So far, its suitability for separation of heavy metal ions and polymers (both natural and synthetic) has been examined [14,15]. This paper describes for the first time the use of C/SiO 2 composite for adsorptive removal of basic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…This carbonaceous material obtained from biomass is usually characterized by high adsorption capacity relative to inorganic and organic substances [ 16 , 17 , 18 ]. Mixed adsorbents may be used in wastewater treatment and soil remediation technologies [ 19 , 20 ]. Usually, they are obtained in two steps: mixing mineral with biomass and pyrolysis of prepared mixture at high temperature [ 15 ].…”
Section: Introductionmentioning
confidence: 99%